The Quiet Quitting Phenomenon among State Civil Appa-ratus and Its Implications for the Effectiveness of Personnel Administration at the Regional Development Planning Agency of Sidoarjo Regency - Yuli Ekowati; Ulul Albab; Ika Devy Pramudiana; Sapto Pramono (Dynamics Social : International Journal of Social Sciences and Communication, 2026)
The phenomenon of quiet quitting, defined as employees performing only at the minimum threshold of formal obligations without initiative or meaningful engagement, has emerged as a pressing global issue within bureaucratic governance. This study aims to analyze the manifestation of quiet quitting among the State Civil Apparatus (ASN), identify its contributing factors, and examine its implications for personnel administration effectiveness at the Regional Development Planning Agency (Bappeda) of Sidoarjo Regency. Employing a qualitative approach, data were collected through purposive in-depth interviews with six informants, non-participant observation, and document review. Data analysis utilized the interactive model of Miles, Huberman, and Saldaña (2014), with validity ensured through source and technique triangulation. Findings reveal that quiet quitting manifests across three dimensions of disengagement: physical, characterized by task-completion orientation without extra effort; cognitive, marked by presenteeism and learned helplessness; and emotional, reflected in apathy and avoidance-based work orientation. Contributing factors include career stagnation, imbalanced workload distribution, and insufficient recognition of ASN contributions, all of which represent breaches of the psychological contract. The implications are evident in declining productivity, service quality, and responsiveness. This study contributes to Indonesian public administration literature by documenting “silent normalization” and “contribution invisibility” as novel insights into quiet quitting within local government bureaucracy.